Applying stated-preference methods to improve health systems in sub-Saharan Africa: a systematic review - Brown, Lauren; De Allegri, Manuela (Expert review of pharmacoeconomics and outcomes research, 2017)
Introduction: Sub-Saharan African health systems must balance shifting disease burdens with desires for robust institutions. Stated-preference methods have been applied extensively to elicit health care workers’ preferences and priorities for rural practice. This systematic review characterizes the range of their applications to African health systems problems.Areas covered: A PRISMA protocol was submitted to PROSPERO. Six databases were queried for peer-reviewed articles using quantitative stated-preference methods to evaluate a health systems-related trade-off. Quality was assessed using the PREFS checklist. Seventy-seven articles published between 1996 and 2017 met review criteria. Methods were primarily choice-based: discrete-choice experiments (n = 46), ranking/allocation techniques (n = 21), conjoint analyses (n = 7), and best-worst scaling (n = 3). Trade-offs fell into six ‘building blocks’: service features (n = 27), workforce incentives (n = 17), product features (n = 14), system priorities (n = 14), insurance features (n = 4), and research priorities (n = 1). Five countries dominated: South Africa (n = 11), Ghana (n = 9), Malawi (n = 9), Uganda (n = 9), and Tanzania (n = 8). Discrete-choice experiments were of highest quality (mean score: 3.36/5).Expert commentary: Stated-preference methods have been applied to many health systems contexts throughout sub-Saharan Africa. Studies examined established strategic areas, especially primary health care for women, prevention and treatment of infectious diseases, and workforce development. Studies have neglected the emerging areas of non-communicable diseases.